HISTORY OF THE GEOGRAPHICAL STUDY OF THE KHOREZM OASIS - N.S.P Matyaqubova Nozima Maksatbayevna (Journals Park Publishing, 2025)
This article covers the historical stages of the geographical study of the Khorezm oasis. From the analysis of written sources from the end of the 19th century to the complex archaeological, geomorphological and cartographic studies carried out in the 20th century, the issues of the natural and geographical development of the oasis, irrigation systems and the formation of riverbeds were analyzed on a scientific basis. In particular, the work of the Khorezm archaeological expedition led by S.P. Tolstov, and the approaches of researchers such as A.S. Kes, B.V. Andrianov, Ya.G. Gulyomov and V.I. Vayinberg have provided an in-depth study of the climate, water resources, ethnogeography and desertification processes of the oasis. Historical information about the Amu Darya flowing into the Caspian Sea through its tributary Uzboy is confirmed by archaeological finds.
Keywords: Khorezm oasis, geographical study, Amu Darya, Uzboy, Sarikamysh, Akchadarya, ancient irrigation systems, archaeological expedition, geomorphology, climate change, historical geography.